2023
DOI: 10.3847/1538-4357/acb700
|View full text |Cite
|
Sign up to set email alerts
|

GRB 221009A: A Light Dark Matter Burst or an Extremely Bright Inverse Compton Component?

Abstract: Gamma-ray bursts (GRBs) have been considered as potential very high energy photon emitters due to the large amount of energy released as well as the strong magnetic fields involved in their jets. However, the detection of teraelectronvolt photons is not expected from bursts beyond a redshift of z ≳ 0.1, due to their attenuation with the extragalactic background light (EBL). For these reasons, the recent observation of photons with energies of 18 and 251 TeV from GRB 221009A (z = 0.151) last 2022 October 9 has … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
13
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(18 citation statements)
references
References 88 publications
(87 reference statements)
2
13
0
Order By: Relevance
“…This new discovery opened the observation window of γ-ray emissions of GRBs in the TeV band and confirmed the new radiation mechanism expected by the model, named the IC process (Mészáros & Rees 1994;Dermer et al 2000;Sari & Esin 2001;Zhang & Mészáros 2001). Those discoveries shined a new light on the central engine and radiation mechanism and probed new physics such as LIV and Dark Matter (DM) (Amelino-Camelia et al 1998;Nakagawa et al 2023;González et al 2023). It is unfortunate that the γ-ray emissions at TeV energy were only observed at the afterglow phase of LGRBs.…”
Section: Introductionsupporting
confidence: 54%
“…This new discovery opened the observation window of γ-ray emissions of GRBs in the TeV band and confirmed the new radiation mechanism expected by the model, named the IC process (Mészáros & Rees 1994;Dermer et al 2000;Sari & Esin 2001;Zhang & Mészáros 2001). Those discoveries shined a new light on the central engine and radiation mechanism and probed new physics such as LIV and Dark Matter (DM) (Amelino-Camelia et al 1998;Nakagawa et al 2023;González et al 2023). It is unfortunate that the γ-ray emissions at TeV energy were only observed at the afterglow phase of LGRBs.…”
Section: Introductionsupporting
confidence: 54%
“…Most interestingly, the Large High Altitude Air Shower Observatory (LHAASO) reported more than 5000 very-high-energy photons within the first ∼2000 s after the burst trigger with energies above 500 GeV all the way to 18 TeV, making them the most energetic photons ever observed from a GRB (Huang et al 2022). Various physical models and radiation mechanisms have been proposed to explain the observed 18 TeV photon (Baktash et al 2022;Brdar & Li 2023;Carenza & Marsh 2022;Finke & Razzaque 2023;Galanti et al 2022;González et al 2023;Li & Ma 2023;Ren et al 2023;Sahu et al 2023;Smirnov & Trautner 2022;Troitsky 2022;Xia et al 2022;Zhang et al 2023;Zhao et al 2023;Zheng et al 2023).…”
Section: Introductionmentioning
confidence: 99%
“…This process is a natural by-product of the classical synchrotronemission model, and can account for emission in this energy band. However, it is not clear yet whether this model can explain the broadband data (at all wavelengths), given the strong constraints on the TeV band flux from radio, optical, and X-ray data (González et al 2023;Miceli & Nava 2022). Furthermore, this model cannot explain the 10 TeV energy photons (Huang et al 2022) originally claimed to be observed (González et al 2023;Ren et al 2023;Laskar et al 2023a;Das & Razzaque 2023;Kann et al 2023).…”
Section: Introductionmentioning
confidence: 99%
“…However, it is not clear yet whether this model can explain the broadband data (at all wavelengths), given the strong constraints on the TeV band flux from radio, optical, and X-ray data (González et al 2023;Miceli & Nava 2022). Furthermore, this model cannot explain the 10 TeV energy photons (Huang et al 2022) originally claimed to be observed (González et al 2023;Ren et al 2023;Laskar et al 2023a;Das & Razzaque 2023;Kann et al 2023). On the other hand, it is not clear if photons at these energies were detected 3 and required to explain the observed spectra (LHAASO- Collaboration et al 2023).…”
Section: Introductionmentioning
confidence: 99%